Guiding Action in the framework of the Covid-19 pandemic: Vital and professional projects of the young population (Costa Rican Journal of Guidance & Counseling, 2022)
In the last two years, the transformation of people's daily lives as a result of the pandemic has been highlighted, for this article it is interesting to contextualize through relevant data the personal and educational alterations that young people have suffered. In addition, it is necessary to define the work that can and should be carried out from the discipline of orientation. For this reason, the main objective is to frame the guiding action for the attention of the vital and professional projects of young people within the framework of the pandemic. It is detailed that, despite the adversities, the affectation of feelings, emotions, health, and integral well-being of people, in a hopeful way, the possibility of generating spaces for intervention to identify positive aspects and learning during the time of the pandemic, construction at a professional and personal level, preventively address the consequences of symptoms of stress, anxiety, depression, etc., and encourage the linking of support networks for the benefit of the population. Among the main conclusions, it is mentioned that there is a need for a commitment to implement guiding practices of accompaniment and follow-up with an integrative and humanizing approach, using inter-institutional and multidisciplinary support. It is necessary to strengthen the various support networks of the context through the management of state and local development projects; to carry out research processes with the aim of generating criteria, theoretical and disciplinary development, with and for the young population
Keywords: guidance; youth; pandemic; life projects; professional projects